Analisis Kepuasan Pengguna Website Sekolah SMAN 1 Wangon Menggunakan Metode End User Computing Satisfaction (EUCS) - Fahmi An Naafi; Fikri Aditnya Pratama; Fauzan Dwicah Saputra; Gilang Satria Mahardhika; Ito Setiawan (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
This study aims to evaluate the level of user satisfaction with the website of SMAN 1 Wangon by applying the End User Computing Satisfaction (EUCS) method. This method assesses user satisfaction based on five main dimensions: system quality, information quality, service quality, end user, and individual benefits. Data collection was conducted through questionnaires distributed to students, teachers, and administrative staff. The results of the analysis show that overall user satisfaction is in a good category, although there are some aspects that need to be improved, especially in terms of information and service quality. This research is expected to provide suggestions for further development of the school website, in order to improve user experience and support the learning process.